Impact of levosimendan on efficacy and renal function in acute heart failure according to renal function: A perspective, multi-center, real-world registry - Zhang, Han; Jiang, Li; Fu, Rui; Qin, Ping; Zhang, Xuan; Tian, Tao; Feng, Guang-xun; Yang, Yan-min (Frontiers in Cardiovascular Medicine, 2022)
Objective: Acute heart failure (AHF) is associated with high mortality. Levosimendan, an inodilator, has proved to increase cardiac output and exert renoprotective effect in AHF. Our aim was to investigate the efficacy and renoprotective effects of levosimendan in patients with AHF and different renal function. Methods: This is a prospective, observational, multi-center registry. Patients admitted with AHF between June 2020 and May 2022 and treated with levosimendan during the hospital stay were included. Baseline characteristics, laboratory tests, electrocardiogram (ECG), chest X-ray, 18 echocardiography,and treatment were collected. A 5-point Likert scale was used to document patients’ baseline dyspnea. The estimated glomerular filtration rate (eGFR) was calculated by means of the Modification of Diet in Renal Disease equation. After levosimendan infusion, patients underwent assessment of degree of dyspnea, and levels of brain-type natriuretic peptide (BNP) /N-terminal pro-BNP (NT-pro BNP), and eGFR repeatedly. Results: Among 789 AHF patients who received levosimendan treatment in this study, 33.0 % were female, mean age was 64.9±16.8 years, and mean eGFR was 72.6±32.5 ml/min/m2. The mean score of dyspnea was 3.0±1.0 using 5-point Likert scale before levosimendan infusion. Dyspnea improved in 68.7% patients at 6h after infusion of levosimendan, and in 79.5% at 24h. Lower eGFR was associated with lower efficacy rate after 6h infusion (71.7%, 70.7%, 65.2% and 66.0%, respectively) and after 24h infusion (80.5%, 81.4%, 76.2% and 77.8%, respectively). The levels of BNP or NT-pro BNP were also decreased after levosimendan treatment, and in each eGFR category. Levels of eGFR increased from baseline (72.6±32.5 ml/min/m2) to 12-24h (73.8±33.5 ml/min/m2) and 24-72h (75.0±33.4 ml/min/m2) after starting treatment (p＜0.001). However, the eGFR levels increased only in patients with eGFR lower than 90.0 ml/min/m2. Conclusions: In AHF patients who received levosimendan, degree of dyspnea and levels of BNP or NT-pro BNP were significantly improved, especially in patients with higher eGFR levels. However, levosimendan infusion increase eGFR only in AHF patients with renal dysfunction.